Analisis Pengaruh Pendapatan Nasional terhadap Inflasi: Studi Kasus Indonesia pada Tahun 2022-2024 - Erickson Sinaga; Mario Purba; Wendi Rehan Situmorang; Jogi Situmorang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes the impact of national income on inflation in Indonesia during the 2022-2024 period. Inflation is an economic phenomenon influenced by various factors, one of which is national income. Using regression analysis methods and the latest macroeconomic data, this research evaluates the relationship between national income and inflation rates in Indonesia. The results indicate a significant correlation between national income growth and changes in inflation levels. These findings are expected to provide insights for policymakers in designing more effective economic strategies to maintain price stability and economic growth.